Hubungan Konflik Peran Ganda, Dukungan Sosial Dengan Kinerja Pns Wanita Di Dinas Kesejahteraan dan Sosial Provinsi Sumatera Utara - Sarumaha, Mariam Ratna Kirana; Rahayu, Ety (UI Scholars Hub, 2014)
Background of this research is based on the increasing opportunities for women to work. The aims of this research are to find out correlation between double role conflict with performance, and correlation between social support with performance of women civil servants at Social Welfare Office in Province of North Sumatra. Which is done at 85 respondents in 99 total respondents, this research indicates that correlation between double role conflict with performance, through Gamma test, has intermediate or enough degree of association in -0,423 and not be significant. Whereas, correlation between social support with performance, through Gamma test, has intermediate or enough degree of association in 0,470 and significance.